2021
DOI: 10.1002/bies.202000319
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic movement stimulates joint formation and development: Implications in arthrogryposis multiplex congenita

Abstract: Arthrogryposis multiplex congenita (AMC) is a heterogeneous syndrome where multiple joints have reduced range of motion due to contracture formation prior to birth.A common cause of AMC is reduced embryonic movement in utero. This reduction in embryonic movement can perturb molecular mechanisms and signaling pathways involved in the formation of joints during development. The absence of mechanical stimuli can impair joint cavitation, resulting in joint fusion, and ultimately eliminate function. In turn, mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…Understanding the responsiveness of external articular morphology to activity and loading, both during development and after maturation, is essential when considering sources of variation in joint morphology. The precise mechanisms of joint morphogenesis remain elusive, but researchers have suggested that a combination of biochemical and mechanical inputs are responsible for the morphological complexities of the adult joint (Carter & Wong, 1988; Chijimatsu & Saito, 2019; Frost, 1979; Hamrick, 1999; Plochocki et al, 2009; Rolfe et al, 2018; Zhou, 2021). Indeed, the main adaptive trajectories experienced during postnatal growth by the joint surfaces may be best explained by chondral modeling theory (Frost, 1979; Hamrick, 1999), which argues that varying degrees of hydrostatic pressure within the joint capsule shape the cartilage anlage so that the opposing articular surfaces remain semi‐congruent to one another in a way that maintains functional integrity of the joint.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the responsiveness of external articular morphology to activity and loading, both during development and after maturation, is essential when considering sources of variation in joint morphology. The precise mechanisms of joint morphogenesis remain elusive, but researchers have suggested that a combination of biochemical and mechanical inputs are responsible for the morphological complexities of the adult joint (Carter & Wong, 1988; Chijimatsu & Saito, 2019; Frost, 1979; Hamrick, 1999; Plochocki et al, 2009; Rolfe et al, 2018; Zhou, 2021). Indeed, the main adaptive trajectories experienced during postnatal growth by the joint surfaces may be best explained by chondral modeling theory (Frost, 1979; Hamrick, 1999), which argues that varying degrees of hydrostatic pressure within the joint capsule shape the cartilage anlage so that the opposing articular surfaces remain semi‐congruent to one another in a way that maintains functional integrity of the joint.…”
Section: Introductionmentioning
confidence: 99%
“… 42 44 During embryonic development, joint movements ensure that the osteochondral interface is correctly formed and that chondrocytes become hypertrophic in the subchondral region. 45 , 46 Further in vitro research has also shown that 3D chondrocyte cultures have a phenotype closer to in vivo behaviour when subjected to intermittent dynamic loading. 47 In vitro 3D chondrocyte cell cultures have been subjected to a wide range of cyclic compressive strains, ranging from higher levels such as 10% 47 to lower 5% 44 and 1%–3%.…”
Section: Key Parameters In Biofabrication Of Osteochondral Tissue Unitsmentioning
confidence: 99%
“…Presumably, the most proximate influence on joint morphology is the shape of neighboring morphology with which it must directly articulate (Carter & Wong, 1988; Chijimatsu & Saito, 2019; Zhou, 2021). For a joint to fulfill its functional role, its conarticular surfaces must grow into shapes and sizes that result in some degree of conformity.…”
Section: Introductionmentioning
confidence: 99%
“…Presumably, the most proximate influence on joint morphology is the shape of neighboring morphology with which it must directly articulate (Carter & Wong, 1988;Chijimatsu & Saito, 2019;Zhou, 2021).…”
mentioning
confidence: 99%